Coracoid or Clavicle Fractures Associated With Coracoclavicular Ligament Reconstruction. Issue 12 (October 2021) - Panarello, Nicholas M.; Colantonio, Donald F.; Harrington, Colin J.; Feeley, Scott M.; Bandarra, Tahler D.; Dickens, Jonathan F.; Kilcoyne, Kelly G.
Background: Coracoclavicular (CC) ligament reconstruction is a commonly performed procedure for high-grade acromioclavicular (AC) joint separations. Although distal clavicle and coracoid process fractures represent potential complications, they have been described in only case reports and small case series. Purpose: To identify the incidence and characteristics of clavicle and coracoid fractures after CC ligament reconstruction. Study Design: Case series; Level of evidence, 4. Methods: The US Military Health System Data Repository was queried for patients with a Current Procedural Terminology code for CC ligament repair or reconstruction between October 2013 and March 2020. The electronic health records, including patient characteristics, radiographs, operative reports, and clinical notes, were evaluated for intraoperative or postoperative clavicle or coracoid fractures. Initial operative technique, fracture management, and subsequent clinical outcomes were reviewed for these patients. Results: A total of 896 primary CC ligament repairs or reconstructions were performed during the study period. There were 21 postoperative fractures and 1 intraoperative fracture in 20 patients. Of these fractures, 12 involved the coracoid and 10 involved the clavicle. The overall incidence of fracture was 3.81 fractures per 1000 person-years. In 5 patients who sustained a fracture, bone tunnels were not drilled in the fractured bone during the index procedure. A total of 17 fractures were ultimately treated operatively, whereas 5 fractures had nonoperative management. Of the 16 active-duty servicemembers who sustained intraoperative or postoperative fractures, 11 were unable to return to full military duty after their fracture care. Conclusion: Fracture of the distal clavicle or coracoid process after CC ligament repair or reconstruction is a rare but serious complication that can occur independent of bone tunnels created during the index procedure. Fractures associated with CC ligament procedures occurred at a rate of 2.46 per 100 cases. Most patients were ultimately treated surgically with open reduction and internal fixation or revision CC ligament reconstruction. Although the majority of patients with intraoperative or postoperative fractures regained full range of motion, complications such as anterior shoulder pain, AC joint asymmetry, and activity-related weakness were common sequelae resulting in physical limitations and separation from military service.